The Ranking Of The Best Educators By Applying Fuzzy Logic Sugeno Based On Performance Assessment - HENDRA CIPTA (INFOKUM, 2021)
In improving the quality of education, mastery of the material is one of the important elements that must be considered by teachers and students. In addition, improving the quality of education is carried out by improving facilities and infrastructure, increasing the professional staff, teaching staff, and improving the quality of students. The purpose of this research was to determine the best educators based on performance assessment. Indicators research refer to PP. No. 19 of 2005 concerning Standar Nasional Pendidikan (SNP) namely knowledge, attitudes, communication, and professionalism. In this case, fuzzy logic Sugeno method is used to rank the best educators in their field. The results showed that there were 3 best educators, namely educator B ranked 1 with an assessment result of 2.25, educator C got rank 2 with an assessment result of 1.65 and educator A with an assessment result of 0.65 got rank 3. It is hoped that with the application of this method, the school can be more effective in assessing educators by adding more indicators to be assessed later.